Critical forces at fractional matching fields in superconducting thin films with triangular pinning lattice - Vizarim, Nicolas Porto [UNESP]; Carlone, Maicon [UNESP]; Verga, Lucas Garcia; Venegas, Pablo Antonio [UNESP] (FapUNIFESP (SciELO), 2017)
We numerically study the commensurability effects in the critical forces in a type II superconducting thin film with vortices under the influence of a triangular pinning lattice at sub matching fields and zero temperature. The analysis is made applying a transport force in two mutually perpendicular directions and magnetic field perpendicular to the film surface. The results show critical force peaks at fractional matching fields, as a direct consequence of the commensurability effects. For the first time, we simulate the sequence of force peaks detected in recent experiments. Anisotropic effects in the critical forces are also reported, in analogy with that found at higher fields.
Keywords: Commensurability; Critical forces; Superconductivity; Vortex pinning